The Taguchi Approach in Studying and Optimizing the Electro-Fenton Oxidation to Reduce Organic Contaminants in Refinery Wastewater Using Novel Electrodes - Abbas, R. N.; Abbas, A. S. (Engineering, Technology & Applied Science Research, 2022)
This study investigated the degradation of organic pollutants using an advanced electrochemical oxidation technique in a batch reactor cell consisting of a graphite anode, modified by electrodeposition of PbO2, and a graphene-modified carbon fiber cathode. The experiment was designed by the Taguchi design approach with an orthogonal array of L18 to study and optimize the degradation of Chemical Oxygen Demand (COD) by the electro-Fenton oxidation process. Four process parameters, Current Density (CD), Temperature, Fe2+ concentration, and time were measured at different levels. The impact of each factor was analyzed by analysis of variance (ANOVA). Furthermore, a linear model analysis was applied for the Signal-to-Noise (S/N) ratio and mean values, obtaining the optimal conditions. The most significant parameter of the COD removal efficiency was time, and the least one was temperature.